2016
DOI: 10.1155/2016/8016186
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathological Features of Canine Myocarditis Associated withLeishmania infantumInfection

Abstract: Myocarditis associated with infectious diseases may occur in dogs, including those caused by the protozoa Neospora caninum, Trypanosoma cruzi, Babesia canis, and Hepatozoon canis. However, although cardiac disease due to Leishmania infection has also been documented, the immunopathological features of myocarditis have not been reported so far. The aim of this study was to examine the types of cellular infiltrates and expression of MHC classes I and II in myocardial samples obtained at necropsy from 15 dogs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 31 publications
5
31
0
2
Order By: Relevance
“…Cardiac involvement in dogs (3,6,7,17) revealed that this protozoan might be also involved in heart, which promptly support the necessity of cardiac evaluation in cases of suspected leishmaniasis.…”
mentioning
confidence: 56%
See 3 more Smart Citations
“…Cardiac involvement in dogs (3,6,7,17) revealed that this protozoan might be also involved in heart, which promptly support the necessity of cardiac evaluation in cases of suspected leishmaniasis.…”
mentioning
confidence: 56%
“…La enfermedad puede existir subclínicamente o puede manifestarse como una afección sistémica [lesiones cutáneas, oculares o renales, hepatoesplenomegalia, anemia, atrofia muscular y pérdida de peso] (2). En los últimos 15 años se han reportado signos clínicos de enfermedad cardiaca en relación con leishmaniasis (3)(4)(5)(6), pudiendo existir lesiones miocárdicas (3)(4)(5)(6)(7), por lo que se pudo detectar el parásito en el tejido cardíaco (3,4,6).…”
Section: Introduccionunclassified
See 2 more Smart Citations
“…Regarding ventricular repolarization, 50% of the dogs afflicted by cytopenic CME presented higher values for the T-wave, exceeding the rates described for animals afflicted by non-cytopenic CME [9]. This may be explained by the profile of anemia and heart disease.…”
Section: Discussionmentioning
confidence: 99%